MICROECONOMIC FACTORS OF THE DEVELOPMENT OF ENTERPRISES AS PERCEIVED BY RURAL ENTREPRENEURS OF THE MAŁOPOLSKIE PROVINCE - Żmija, Katarzyna (Acta Scientiarum Polonorum. Oeconomia, 2017)
The article analyses evaluation of rural entrepreneurs concerning selected factors of development of their business. Attention was paid to the microeconomic factors relating to the resources available to the companies and the local conditions. Factors that are, in the opinion of entrepreneurs, drivers of growth included the location of the business, the availability of the Internet, the way the company is managed, access to the target recipients of services and products, technologies used, the number of customers covered by the activities of the company, as well as competencies, knowledge and skills of the owner-manager. The most frequently cited barriers limiting the development of activity of the surveyed entrepreneurs were their capital resources and the level of intensity of market competition.